ANALYSIS OF QUALITY CONTROL WITH METHOD STATISTICAL PROCES CONTROL (SPC) BOX CULVERT AT PT. LUTVINDO WIJAYA PERKASA PEKANBARU - Muhamad Enzho Aryadipo; Auzar Ali; Hendrizal Hendrizal (STIE Bangkinang Publishing, 2021)
This study aims to analyze whether the application of the product quality control system at PT. Lutvindo Wijaya Perkasa pekanbaru. With the total production data for box culvert products from January to July 2019, there are 20 defective products from the total production of 488 with a percentage of damage of 4.08%. The technique of collecting data using the method of interviewing, observation, and documentation at the company. Data processing is performed using tools found in Statistical Process Control (SPC). Based on the results of research with the Control Chart and Fishone Diagram. Based on calculations with the Control Chart, it has a control limit, namely the lower control limit (LCL) 3.02 and the upper control limit (UCL) 11.02. Based on the results of the fishone diagram analysis, it is known that the factor causing product defects is Human.